An empirical study on factors influencing the effectiveness of algorithm visualization - Lazaridis, Vassilios; Samaras, Nikolaos; Sifaleras, Angelo (Computer applications in engineering education, 2013)
The determination of the factors influencing the effectiveness of algorithm visualization poses an interesting research question. In this paper, we present the results of a longitude empirical study regarding this question. The study was based on an evaluation of the Visual LinProg educational tool inside classrooms. Visual LinProg is a web‐based educational tool, which solves linear programming problems using animation and visualization techniques. Visual LinProg was developed to be used in linear programming courses to supplement the teaching. Our empirical study is based on questionnaires that include quantitative and qualitative topics. This evaluation first indicates that Visual LinProg facilitates the learning of the revised simplex algorithm and second presents more results on factors influencing the understanding of this algorithm by the students/users of the Visual LinProg. © 2010 Wiley Periodicals, Inc. Comput Appl Eng Educ 21: 410–420, 2013